THE TEACHING BY YOUR LEAVE EXPLOITATION EFFECT FROM ROUTINE - VASILÍKOVÁ, Daniela (Trends in education, 2009)
The script-writer was represented actual problems at natural educated I want to submit a proposal servive and application systematic way to instruct physical education. The idea is exploitation relation interim educational study.
Keywords: Problems educated at natural philosophy. The teaching by your leave exploitation effect from routine. Actual educated physical system in Slovak secondary schools.